2021
DOI: 10.1016/j.conctc.2021.100698
|View full text |Cite
|
Sign up to set email alerts
|

Does prospective acceptability of an intervention influence refusal to participate in a randomised controlled trial? An interview study

Abstract: Background The generalizability of findings of Randomised Controlled Trials (RCTs) is undermined by low or biased recruitment. Reasons for participant refusal are infrequently reported in published literature. Aims To apply the Theoretical Framework of Acceptability (TFA) to: (1) explore patient-reported reasons for declining to participate in a RCT comparing a new service model (patient-initiated appointments) with standard care (appointments scheduled by clinician) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 32 publications
(35 reference statements)
1
20
0
Order By: Relevance
“…Feeney et al described anticipated burden as the burden of spouse caregivers who perceived their partners in severe health conditions in the future [ 19 ]. Sekhon et al studied defined anticipatory burden in a random control trial (RCT) as the accessibility of the intervention and the required amount of effort for participation [ 20 ]. Notably, in this study, the concept of anticipatory burden was utilized to determine if low accessibility is a significant factor leading to reduced participation or non-adherence to the intervention among the participants.…”
Section: Resultsmentioning
confidence: 99%
“…Feeney et al described anticipated burden as the burden of spouse caregivers who perceived their partners in severe health conditions in the future [ 19 ]. Sekhon et al studied defined anticipatory burden in a random control trial (RCT) as the accessibility of the intervention and the required amount of effort for participation [ 20 ]. Notably, in this study, the concept of anticipatory burden was utilized to determine if low accessibility is a significant factor leading to reduced participation or non-adherence to the intervention among the participants.…”
Section: Resultsmentioning
confidence: 99%
“…Data from the study however suggests that participants were equally as confident in this new model of care as treatment as usual, and could meet the needs of over a third of patients who would prefer a shorter or longer treatment schedule than the typical 12 weeks. A more in-depth understanding of the acceptability of the new treatment model, has been further analyzed in a qualitative study and is reported elsewhere [ 33 ]. The views of healthcare professionals within the dystonia service would also be valuable to future implementation efforts and an in-depth understanding of their beliefs could be obtained from future research.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluating prospective acceptability is valuable because it can influence participation and uptake rates [ 14 ], and we recommend that this is routinely included in implementation. Only one-third of the WASH studies evaluated the prospective acceptability of the interventions; fewer still used this information to influence the design or implementation of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The ‘acceptability’ of an intervention is a key component of implementation [ 13 ]. This is because acceptability can influence initial uptake, and sustained use of an intervention [ 14 ]. Sekhon et al recently developed the theoretical framework of acceptability (TFA) for healthcare interventions [ 15 ].…”
Section: Introductionmentioning
confidence: 99%